The Effect of Stabilization-based Program on Anxiety in Elderly Patients with Generalized Anxiety Disorder - Supphasri, Kanjana; Kongsuwan, Vineekarn; Nukaew, Orawan (Journal of Phrapokklao Nursing College, Chanthaburi, 2024)
This quasi-experimental research aimed to examine the effect of stabilization-based program on anxiety in elderly patients with generalized anxiety disorder. The participants were 60 elderly patients with generalized anxiety disorder undergoing treatment at a hospital in the southern region of Thailand and were equally divided into an experimental group (n = 30) and a control group (n = 30). The research instruments included the stabilization-based program, the Ruminative Response Scale (RRS) with a reliability of .83, the State-Trait Anxiety Inventory (STAI form Y) with the reliabilities of .82 and .83, the Modified Barthel Activities of Daily Living Index (BAI), the Mini-Mental State Examination: Thai version (MMSE–Thai 2002), and a demographic data form. The implementation and data collection were conducted from February to April 2022. Data were analyzed using frequency, percentage, mean, standard deviation, Chi-square test, paired t-test, and independent t-test. The research results revealed that 1) after the experiment, the experimental group had statistically significantly lower mean scores of state-anxiety and trait-anxiety than those of before the experiment (t = 9.190, p < .001 and t = 9.390, p < .001, respectively); and 2) after the experiment, the experimental group had statistically significantly lower mean scores of state-anxiety and trait-anxiety than those of the control group (t = 5.710, p < .001 and t = 10.880, p < .001, respectively). This research suggests that psychiatric nurses should adopt the stabilization-based program to care for elderly patients with generalized anxiety disorder, in order to reduce anxiety and prevent the mental health crisis.